2019
DOI: 10.3390/ijgi8120583
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical, Social, and Housing Disorder on Neighborhood Crime: A Contemporary Test of Broken Windows Theory

Abstract: The current study tests neighborhood (i.e., block group) effects reflective of broken windows theory (i.e., neighborhood, public space, social, housing disorder) on crime. Furthermore, these effects are tested independently on serious (i.e., Part I), and less serious (i.e., Part II) crime rates. Disorder data on a racially/ethnically stratified sample of block groups (N = 60) within Milwaukee, Wisconsin, U.S.A. were collected through systematic observations. Using these data, along with census and crime data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2027
2027

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Studies of broken windows have generally focused on the relationships between disorder and crime (e.g., see Konkel, Ratkowski, and Tapp 2019;Sampson and Raudenbush 1999;Taylor 2001;Vilalta et al 2020, Yang 2010 and have seldom examined the intervening mechanism of informal social controls in the community (for reviews, see Braga et al 2015;Hinkle 2013;Weisburd et al 2015). In our view, examining the direct relationship between disorder and crime is not the correct test of Wilson and Kelling's theoretical model, as they are clear that informal social control in the community is the key mechanism through which crime is reduced (see also, Bratton and Kelling 2006;Gault and Silver 2008;Weisburd et al 2015;Weisburd, White, Wire, and Wilson 2021;Xu, Fiedler, and Flaming 2005).…”
Section: Broken Windows and Community Social Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of broken windows have generally focused on the relationships between disorder and crime (e.g., see Konkel, Ratkowski, and Tapp 2019;Sampson and Raudenbush 1999;Taylor 2001;Vilalta et al 2020, Yang 2010 and have seldom examined the intervening mechanism of informal social controls in the community (for reviews, see Braga et al 2015;Hinkle 2013;Weisburd et al 2015). In our view, examining the direct relationship between disorder and crime is not the correct test of Wilson and Kelling's theoretical model, as they are clear that informal social control in the community is the key mechanism through which crime is reduced (see also, Bratton and Kelling 2006;Gault and Silver 2008;Weisburd et al 2015;Weisburd, White, Wire, and Wilson 2021;Xu, Fiedler, and Flaming 2005).…”
Section: Broken Windows and Community Social Controlmentioning
confidence: 99%
“…Despite explicitly different images and meanings between social disorder (e.g., drug activities, group of kids causing problems) and physical disorder (e.g., buildings with broken windows, litter, graffiti), most studies examining the role of disorder in the mechanisms of the broken windows thesis have used a general disorder measure rather than separated measures of social disorder and physical disorder (for exceptions, see Hinkle 2013, 2015; O’Brien and Ciomek, 2022; Sampson and Raudenbush 1999; Ward et al 2017). Thus, we know little about how social disorder and physical disorder differentially influence informal social controls in the community, though some studies have identified differential impacts of social disorder and physical disorder on diverse outcomes known to be related to informal social controls in the community, such as physical outdoor activity (Molnar, Gortmaker, Bull, and Buka 2004) and fear of crime (Hinkle 2015; Kuen, Weisburd, White, and Hinkle 2022).…”
Section: Broken Windows and Community Social Controlmentioning
confidence: 99%
“…But people also differ substantially in their responses to the same instances of 'disorder,' with some positive and pro-social interpretations-such as graffiti as an indicator of a creative community (Wallace & Louton, 2018). Social disorder in particular appears to generate a diversity of interpretations (Konkel et al, 2019;Yang & Pao, 2015). People may not distinguish perceptions of disorder and crime (Gau & Pratt, 2008).…”
Section: Objective Versus Subjective (And Measurement)mentioning
confidence: 99%
“…Similarly, [126], pointed out that the degree of social and physical disorder and the design of the building environment influence the fear of crime, while real crime events are affected by patterns of land use and the existence of particular buildings, such as the railways. Moreover, neighborhoods that have increasing disorder frequencies can benefit from strengthened partnerships among law enforcement officials, community members and other local stakeholders to dissuade offenses at all levels and thus decrease disorder and crime indicators [77].…”
Section: Perception Of Neighborhood Crimementioning
confidence: 99%